Pengaruh Kualitas Audit Terhadap Hubungan Pengungkapan Other Comprehensive Income Dengan Relevansi Nilai Informasi Akuntansi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Firman Surya; Rangga Putra Ananto; Dita Maretha Rissi (Akuntansi dan Manajemen, 2018)
OCI components contain high assumptions, estimates and judgments from managements, therefore, high quality audits may improve the value relevance of OCI. The aims of this research is to analyze the effects of audit quality on relationship of other comprehensive income disclosure with value relevance of accounting information on companies listed in Indonesia Stock Exchange for 2014-2016. Other comprehensive income as independent variable is measured by OCI ratio. Methods of data analysis in this research using multiple linear regression analysis. The results of this research show that the disclosure of other comprehensive income that supported by audit quality may increase the value relevance of accounting information. This results obtained from the F test significant value of 0.000 (<0.05) with the level of influence of 24.1% as evidenced by the value of adjusted R2. Based on the results of the research are expected to related parties in the capital market may encourage capital market participants to optimize the information contained in the financial statements, including information on other comprehensive income.